2011
DOI: 10.4103/0253-7176.92068
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Modeling its Risk Factors in Medical Students, Iran

Abstract: Background:Today's internet is a usual and common method for identifying and fulfilling unknown practices. Internet network has been prepared rapid and comfortable access to information. Internet addiction is a new and attractive subject that has been regarded as behavior-based addiction recently.Purpose:To estimate the prevalence of internet addiction and some of the related factors among medical students, Iran.Materials and Methods:An analytical cross-sectional study was conducted on 426 students selected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
73
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 17 publications
16
73
6
2
Order By: Relevance
“…The validity of the questionnaire was confirmed by Content Validity Index (CVI = 0.78) for each item by 3 experts, and its reliability was approved using test-re-test (r = 0.88) in a 2-week interval by 20 medical sciences students and Cronbach's alpha (α = 0.87). Also, the reliability and validity of this instrument have been demonstrated in previous studies (12)(13)(14).…”
Section: Internet Addiction and Mental Health Measurementsupporting
confidence: 52%
See 2 more Smart Citations
“…The validity of the questionnaire was confirmed by Content Validity Index (CVI = 0.78) for each item by 3 experts, and its reliability was approved using test-re-test (r = 0.88) in a 2-week interval by 20 medical sciences students and Cronbach's alpha (α = 0.87). Also, the reliability and validity of this instrument have been demonstrated in previous studies (12)(13)(14).…”
Section: Internet Addiction and Mental Health Measurementsupporting
confidence: 52%
“…While the study was conducted among medical students of Guilan, IA was lower among nursing students (5). In another study, a significant relationship was not found between major and IA (20).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results of research conducted in the United States show that the use of the Internet among young people is higher than any other age group (4). Several countries in Asia, especially China, South Korea, and Taiwan have the highest prevalence of Internet addiction among young people (5). new kind of addiction, the Internet addiction, has been emerged as the problem of the communication age (6).…”
Section: Introductionmentioning
confidence: 99%
“…(Aboujaoude, 2010;Ayatollahi, 2010;Swaminath, 2008;Dargahi, 2007). This use is increasing with time, such enormous use is not without negative effects, like its detrimental effect on academic performance, social isolation and psychological problems (Subramaniam, 2008).…”
Section: Introductionmentioning
confidence: 99%